2020
DOI: 10.1515/ntrev-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mechanical properties of epoxy/nanohybrid composites by nanoindentation

Abstract: AbstractThe carbon nanofibers and molybdenum disulfide (CNF-MoS2) nanohybrid material was fabricated and incorporated into epoxy resin to form the nanocomposite coating. Firstly, microstructure observation shows that each CNF was uniformly wrapped up with MoS2 nanosheets, and the nanohybrids were well dispersed in the coating. Then, nanoindentation experiments were carried out to explore the effect of the CNF-MoS2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In unloading stage, relative to the other three curves, the TPI‐6 had lower residual depth (~448 nm), the main reason was that it was more elastic 25 . The incorporation of the PBO‐MoS 2 hybrids in TPI matrix can form a three‐dimensional structure, When the composites suffered the load from the indenter, because of the hybrids had better dispersity and larger specific surface area, it would share part of the stresses, resulting to the reduced pressure on polymer matrix, then the bearing capacity, hardness and elastic modulus of composites would be improved 26 . The composites with higher hardness can have better bearing capacity and prevent the polymer matrix from being worn off.…”
Section: Resultsmentioning
confidence: 99%
“…In unloading stage, relative to the other three curves, the TPI‐6 had lower residual depth (~448 nm), the main reason was that it was more elastic 25 . The incorporation of the PBO‐MoS 2 hybrids in TPI matrix can form a three‐dimensional structure, When the composites suffered the load from the indenter, because of the hybrids had better dispersity and larger specific surface area, it would share part of the stresses, resulting to the reduced pressure on polymer matrix, then the bearing capacity, hardness and elastic modulus of composites would be improved 26 . The composites with higher hardness can have better bearing capacity and prevent the polymer matrix from being worn off.…”
Section: Resultsmentioning
confidence: 99%
“…An indenter in the nanoindenter, controlled by a high-resolution instrument, penetrates the surface of the material with a certain rate and afterward unloaded. Hardness and modulus were calculated using load-displacement data obtained through loading-unloading cycles [21]. In 2007, Lee et al measured the hardness and modulus of the fiber-reinforced polymeric composite [21].…”
Section: Introductionmentioning
confidence: 99%
“…Hardness and modulus were calculated using load-displacement data obtained through loading-unloading cycles [21]. In 2007, Lee et al measured the hardness and modulus of the fiber-reinforced polymeric composite [21]. In 2017, Kavouras et al explored the effect of microstructure on the fiber-based composite using nanoindentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of novel composite materials is important for improving the material performance [17][18][19]. For instance, carbon nanomaterials have been widely used as a functional additive in polymers to improve the mechanical, electrical, and thermal properties of nanocomposites [20][21][22][23]. Recently, reports have indicated that the mechanical strength and electro-response characteristics of EAHs could be improved by adding electro-active components, such as graphene [24] and multi-walled carbon nanotubes (MWCNTs) [25], to the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%